The Geographic Characteristics of Urban System in the Governorate of Lattakia (Syria) 2011. - Wazzan, Kinda (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
In this study the urban system of the governorate of Lattakia has been examined through the applicability of measurements of the equality of spatial distribution patterns of cities (Demangeon Index and Lorenz curve), and those of Primacy and cities size distribution patterns (the Law of Primate city of Mark Jefferson, 1939, the Index of Primacy of Stewart, and the hierarchical order of city through the Rank-size Rule - George, K. Zipf, 1949). It has been identified on the size of the imbalance equilibrium in the system urban cities through Urban Isostastic Index. The results of the study showed a clustered patterns of the spatial distribution of urban centers according to the value of Demangeon Index (0.42) and unequal distribution of urban population to the cities (75% of urban population are distributed on 15% of cities). It showed also a great domination of the primate city of Latakia on the urban system where the population volume was (6.1) time bigger than the volume of the next cities according to Primacy Index; a great decrease of the real value of the next cities comparing with the theoretical value of Law of Primate City (16.4%) against (67%), and disability to applying the Rank-size Rule.